2013
DOI: 10.1021/jp408207u
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Effect of Sn on CO and Formic Acid Oxidation at PtSn Catalysts

Abstract: The role of Sn on the catalytic activity for CO and formic acid oxidation is studied by comparing the activities of differently treated PtSn/C and Pt/C catalysts. The catalysts are prepared by a microwave-assisted polyol synthesis method. As revealed by scanning tunneling and transmission electron microscopic (STM and TEM) characterization, the outcomes of the synthesis procedure for both Pt and PtSn are small particles, ∼1.5 nm in diameter. Upon deposition on the carbon support, the particle size increases to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 64 publications
10
43
0
1
Order By: Relevance
“…Hence, the surface reconstructs and becomes very rough and full of defects. In this new surface, Sn is present only in the subsurface layers [20]. On the other hand, in the same work, the authors also showed that the degradation of these structures results in a significant loss of ECSA [20], such as we observe in the present case.…”
Section: Surface Characterization After Successive Oxidation Cyclessupporting
confidence: 82%
See 4 more Smart Citations
“…Hence, the surface reconstructs and becomes very rough and full of defects. In this new surface, Sn is present only in the subsurface layers [20]. On the other hand, in the same work, the authors also showed that the degradation of these structures results in a significant loss of ECSA [20], such as we observe in the present case.…”
Section: Surface Characterization After Successive Oxidation Cyclessupporting
confidence: 82%
“…In this new surface, Sn is present only in the subsurface layers [20]. On the other hand, in the same work, the authors also showed that the degradation of these structures results in a significant loss of ECSA [20], such as we observe in the present case. Here, the loss of ECSA is particularly evident for those electrodes richer in Sn, as shown in Table 2.…”
Section: Surface Characterization After Successive Oxidation Cyclessupporting
confidence: 82%
See 3 more Smart Citations